Analisis Paparan Iklim Kerja Pada Praktikan Di Laboratorium Mesin Listrik PPNS - Devina Livia Hendriani; Keyne Nabila Regi; Stevan Rizky Marisi Girsang; Dika Rahayu Widiana; Denny Oktavina Radianto (KOLONI, 2024)
The PPNS (Surabaya State Shipping Polytechnic) electrical engineering laboratory is a laboratory used by practitioners or students to carry out college learning activities that are closely related to electricity. Activities carried out by practitioners will of course expend energy which can later result in fatigue and even dehydration, so it is necessary to conduct an analysis of exposure to the work climate in the practicum area. The definition of work climate according to Davis (2002:21) says that work climate is defined as the human environment in which workers or organizations do work and its existence is something that cannot be touched or seen but is there. Therefore, this research was conducted to create comfortable conditions or atmosphere for practitioners to carry out learning activities in the PPNS electrical machine laboratory. A comfortable work environment can increase productivity, efficiency and effectiveness of work and reduce occupational diseases (NAB).